2018
DOI: 10.1080/0142159x.2018.1445207
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional training: Start with the youngest! A program for undergraduate healthcare students in Geneva, Switzerland

Abstract: A very first evaluation of the teaching and learning and particularly on the aspects of acquisition of collaborative tools shows positive attitudes of students towards the implementation of this new training program. Furthermore, a pre-post questionnaire on teamwork aspects reveals significant modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 9 publications
1
24
0
5
Order By: Relevance
“…The inculcation of test‐enhanced learning practices, also known as retrieval practice (Desy et al, ; Rutledge et al, ), is another effective strategy that has been reported to nurture the learning efforts of health care students. It directly supports the quest for instant success (Dornan et al, ; de Paiva et al, ; Gauer and Jackson, ) that often drives millennial students to maximize the benefits of their study efforts (Barie and Ho, ; Ezell et al, ; van Gessel et al, ). Test‐enhanced learning practice bolsters this concept as it involves recalling information through questions (Cerasoli and Ford, ; Coyne et al, ) or other testing procedures (Zumwalt et al, ; Gliddon and Cridge, ; Barrett et al, ).…”
Section: Stimulating Intrinsic Motivation In Millennial Studentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The inculcation of test‐enhanced learning practices, also known as retrieval practice (Desy et al, ; Rutledge et al, ), is another effective strategy that has been reported to nurture the learning efforts of health care students. It directly supports the quest for instant success (Dornan et al, ; de Paiva et al, ; Gauer and Jackson, ) that often drives millennial students to maximize the benefits of their study efforts (Barie and Ho, ; Ezell et al, ; van Gessel et al, ). Test‐enhanced learning practice bolsters this concept as it involves recalling information through questions (Cerasoli and Ford, ; Coyne et al, ) or other testing procedures (Zumwalt et al, ; Gliddon and Cridge, ; Barrett et al, ).…”
Section: Stimulating Intrinsic Motivation In Millennial Studentsmentioning
confidence: 99%
“…However, testing in any form always evokes a certain amount of anxiety in students (Miller, ; Raza et al, ), as it is perceived by them as an evaluation of their knowledge (Walker et al, ; Ames et al, ; Manzi et al, ) or understanding (Younan, ; Khalil et al, ) of a particular topic based on their performance. Hence, test‐enhanced learning practices should emphasize no‐stakes or low‐stakes scenarios (Karpicke and Bauernschmidt, ; Strombach et al, ; Raza et al, ), where the primary purpose is to enhance recall to promote student learning (Sluka et al, ; van Gessel et al, ). In addition, such test‐enhanced learning practices should specifically align with predetermined course objectives to offer students opportunities to practice important skills (Rogers and Tutty, ; Schubert, ; Yan et al, ), analyze complex situations (Elmore et al, ; Woolley and Fishbach, ), and synthesize different points of view (Sinclair et al, ; de Bruin et al, ).…”
Section: Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, the master’s thesis has been introduced between the fourth and fifth academic years to enhance the status of scientific work and critical analysis. In addition, an interprofessional simulation centre was set up in 2013 to provide continuous development of a longitudinal interprofessional curriculum for medical students and students from the health professions of the partner University of Applied Sciences Health [14]. …”
Section: Resultsmentioning
confidence: 99%